Biomarkers of immune dysfunction following combination antiretroviral therapy for HIV infection. (April 2011) - Lichtfuss, Gregor F; Hoy, Jennifer; Rajasuriar, Reena; Kramski, Marit; Crowe, Suzanne M; Lewin, Sharon R
Combination antiretroviral therapy (cART) has significantly reduced morbidity and mortality of HIV-infected patients, yet their life expectancy remains reduced compared with the general population. Most HIV-infected patients receiving cART have some persistent immune dysfunction characterized by chronic immune activation and premature aging of the immune system. Here we review biomarkers of T-cell activation (CD69, -25 and -38, HLA-DR, and soluble CD26 and -30); generalized immune activation (C-reactive protein, IL-6 and D-dimer); microbial translocation (lipopolysaccharide, 16S rDNA, lipopolysaccharide-binding protein and soluble CD14); and immune dysfunction of specific cellular subsets (T cells, natural killer cells and monocytes) in HIV-infected patients on cART and their relationship to adverse clinical outcomes including impaired CD4 T-cell recovery, as well as non-AIDS clinical events, such as cardiovascular disease.